Long-term health-related quality of life in transplant-ineligible patients with newly diagnosed multiple myeloma receiving lenalidomide and dexamethasone. Issue 2 (1st February 2018) - Vogl, Dan T.; Delforge, Michel; Song, Kevin; Guo, Shien; Gibson, Craig J.; Ervin-Haynes, Annette; Facon, Thierry
Abstract: The FIRST trial demonstrated that continuous therapy with lenalidomide and dexamethasone (Rd) prolongs overall survival (OS) and improves health-related quality of life (HRQoL) during the first 18 months of therapy in newly diagnosed multiple myeloma (NDMM) patients. However, patient-reported HRQoL data were not collected after 18 months. We therefore estimated HRQoL scores based on time-varying data collected during progression-free follow-up after 18 months. During the initial 18 months of Rd, observed changes from baseline were within the 95% confidence interval of the predictive models at 33 of 35 time points across 7 HRQoL scores. Predicted scores after 18 months of therapy showed that observed HRQoL improvements during therapy were maintained or improved. Therefore, the survival gain observed with Rd does not come at a cost of declining HRQoL during continuous therapy beyond 18 months, supporting long-term Rd as a standard of care for initial myeloma therapy.